FIRST FIND OF SULFIDES IN CONTACT WITH DIAMONDS IN ECLOGITE XENOLITHS FROM THE UDACHNAYA PIPE - Spetsius Z.V.; Bulanova G.P. (My University, 1989)
As shown by the results of numerous investigations, sulfides appear as inclusions in diamonds in all kimberlite pipes of both the Yakutian and African provinces. Neutron-activation analysis of more than 1500 diamonds from the Premier, Finch and Jagers-fontein pipes also showed that most diamond crystals, even without visible mineral inclusions, contain traces of sulfide material. Study of the mineralogy and the chemistry of sulfides from Yakutian kimberlite pipes indicates that the sulfide minerals in diamonds are similar to those in mantle eclogite. Although any genetic interpretation of the close sulfide-diamond relationship is still far from unequivocal, the existence of sulfide melts during diamond crystallization can no longer be disputed. The fact that they were melts is indicated by the presence in the diamond-bearing eclogite xenoliths of monosulfide solid solutions preserved both within and around diamonds. Most likely, during the natural growth of diamonds, components of the sulfide system as iron and nickel act as metal solvents do during their artificial synthesis.